PENGARUH PEMBERIAN JUS NANAS TERHADAP PENURUNAN KADAR ASAM URAT DI DESA PASAR MERAH TIMUR MEDAN KOTA - AULIA RAHMI PRATIWI; LITA SEPTINA CHANIAGO (JURNAL ILMIAH KOHESI, 2023)
Hyperuricemia is a condition in which blood uric acid levels exceed normal limits, namely 7 mg / dL in men and 6 mg / dL in women. Hyperuricemia can occur due to an increase in uric acid metabolism, when prolonged it can cause gout. Pineapple fruit is an alternative medicine and is easy to obtain and contains flavonoids as antioxidants so that its function to inhibit the work of the enzyme xanthin oxidase which causes purine metabolism to form uric acid will not occur. The purpose of this study identified the effect of pineapple juice on reducing uric acid levels. This study uses a quasi-experimental design with a non-equivalent control group design design. The sample selection technique used in this study was purposive sampling with a total of 32 samples. Data collection techniques by means of observation. Data analysis using wilcoxon and paried T tests. The result of the uric acid levels of the control group in the control group before being given a value with an average value of 7.78 mg / dl, a post-test value with an average of 7.68 mg / dl, uric acid levels in the experimental group in the group before being given pineapple fruit juice an average value of 10.1 mg / dl and uric acid values after being given pineapple fruit juice value average to 5.36 mg / and there was an effect of pineapple juice administration on changes in uric acid levels in Pasar Merah Village East of Medan City with a value of p value = 0.000 (p<0.05. There is an influence of pineapple juice on changes in uric acid levels in Pasar Merah Timur Village, Medan Kota.